Analisis Pengaruh Karakteristik Perusahaan Terhadap Pengungkapan Sukarela - Hendi, Hendi; Feronica, Feronica (Faculty of Economics, Universitas Internasional Batam, 2017)
The purpose of this research is to analyze the effect of firm characteristics (firm size, leverage, ownership concentration, board independence, profitability, age firm, audit firm, industry type, growth opportunity) on voluntary disclosure of listed companies in the Indonesia Stock Exchange. This research used a samples from this study population using the 539 companies listed on the Indonesia Stock Exchange in the period 2011-2015 were selected using purposive sampling method. This study uses Eviews program with panel regression methods to analyze the data.  The results of this study stated that the variable firm size, profitability, age firm, and audit firm has a significant positive effect on voluntary disclosure. While these studies show that the variable leverage, ownership concentration, board independent, industry type and the growth opportunity does not significantly influence voluntary disclosure